Assessment of Cadmium and Plumbum content accumulated in soil and some earthworm species (genus Pheretima) in Hoa Khanh industrial area, Da Nang city - Hong Ha, Pham Thi; Khanh, Nguyen Van; Hieu Giang, Le Thi (Academia Journal of Biology, 2012)
Earthworms are useful and convenient indicators of the ecological health of soil. They are common and easy to sample and identify. They can absorb heavy metals with the large amout into the body without toxicity for body. Therefore they can be used as bioaccumulaters to assess heavy metal pollution in soil of a certain area. Hoa Khanh industrial area is one of the important industrial zones of Da Nang city, where located many factories: steel, mechanical, assembling, garments, electronics, product packaging, agriculture, forestry and seafood processing. Thus, the existence of heavy metal in industrial waste water is inevitable and cause the increase in content of some heavy metals in soil. In this study, we present results of the study on the content of Cd and Pb accumulation in soil and earthworms to help building the scientific basis for using earthworms as a bioindicator of heavy metal pollution (Cd and Pb) in soil. Heavy metals (Pb and Cd) accumulated by earthworm species examined in samples collected between November, 2009 and March, 2010. The means value of heavy metals in soil were 7.05 ± 4.69 mg/kg Cd and 36.05 ± 14.06 mg/kg Pb and these is earthworms were 1.23 ± 0.007 mg/kg Cd and 14.7 ± 2.97 mg/kg Pb (dry weight).